Dhikr As Nursing Intervention to Reduce Stress In Health Science Students - Wahyu Rochdiat M; Erika Hestu; Endang Lestiawati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Study showed that 53% of health sciences students experience stress during the learning process. There has never been any previous research that focused on measuring the effect of Dhikr as a part of independent nursing intervention: Spiritual Support to reduce stress in health sciences students. Aim of this study was to measure stress decreased in health sciences students who were treated using Dhikr. Methods: This research used quasi experimental with pre and post test nonequivalent control group design. We chose Moslem students in health sciences faculty and used quota sampling technique before divided them into two groups: 20 respondents in each of control and intervention groups. Dhikr was given to the treatment group for two sessions, while the control group did not get any therapy. Paired T-Test was used to see stress scores differences in pre and post test of each group, while Mann Whitney test was used to see differences in stress scores deviation between both group. Results: The results showed that Dhikr could decreased stress intervention group (p value 0.000). Stress score mean in pre test was 18.60, while in post test was 11.10 or decreased by 7.5 points. Stress score mean in the control group increased by 3.1 points (p value 0.024). Conclusions: We conclude that Dhikr therapy can be part of independent nursing intervention: Spiritual Support to health sciences students in Indonesia who are predominantly Moslem.